Strategy for Management of Educational Institutions in Developing School Quality - Sri Rahmayanti; Aktar, salim; Supiah Ningsih (Kirana Publisher (KNPub), 2022)
This Study aims to describe the strategy of the foundation's management in developing the quality of elementary school education at Ar Rojaq Kisaran Integrated Islamic Elementary School. This Study uses qualitative methods through observation techniques, interviews, and documentation. The results of this study indicate that the strategy of the foundation's management in developing the quality of education affects strengthening the vision, mission, goals, and strategies carried out in strengthening the quality of education.